Selective Inhibition of an Apicoplastic Aminoacyl‐tRNA Synthetase from Plasmodium falciparum. Issue 4 (27th February 2013) - Hoen, Rob; Novoa, Eva Maria; López, Alba; Camacho, Noelia; Cubells, Laia; Vieira, Pedro; Santos, Manuel; Marin‐Garcia, Patricia; Bautista, Jose Maria; Cortés, Alfred; Ribas de Pouplana, Lluís; Royo, Miriam
Abstract The resistance of malaria parasites to available drugs continues to grow, and this makes the need for new antimalarial therapies pressing. Aminoacyl‐tRNA synthetases (ARSs) are essential enzymes and well‐established antibacterial targets and so constitute a promising set of targets for the development of new antimalarials. Despite their potential as drug targets, apicoplastic ARSs remain unexplored. We have characterized the lysylation system of Plasmodium falciparum, and designed, synthesized, and tested a set of inhibitors based on the structure of the natural substrate intermediate: lysyl‐adenylate. Here we demonstrate that selective inhibition of apicoplastic ARSs is feasible and describe new compounds that that specifically inhibit Plasmodium apicoplastic lysyl‐tRNA synthetase and show antimalarial activities in the micromolar range.